TEKNOLOGI VIRTUAL REALITY MENDUKUNG PROMOSI PERJALANAN INSENTIF DI TRAVELAB POLITEKNIK NEGERI BANDUNG - Abdillah, Abdillah; Noor, Noor; Suryana, Suryana (Ekonomi dan Bisnis, 2017)
Technology is continuing to improve its quality for the users convenience. Virtual Reality (VR) is a technology that allows users who are in the simulation room will feel like in real situations. VR now entering the realm of tourism as media promotion. It uses become important for a travel agent because takes promotion for tourism products and services. One of the travel agents’ products is variety of tour packages, such as travel incentive that focus on business and leisure in one package. TraveLab as a Bandung State Polytechnic travel agent often serve the incentive travel package’ as the student request to visit industries combine with destinations.Selection of VR as a promotional media at TraveLab known as a new media that attracts consumers to get information about tour package in the form of video watch. Along with the student needs and interest to new technology, VR is one of the recent technology that adopt by TraveLab to promote their incentive tour package to its specific segment, that are student of Bandung State Polytechnic. The enhancement of VR as promotional media, need more selection of videos. This project emphasis on the development of varies video of incentive travel package relate to specific student segmentation. The video shoot have been done by 360 degree camera with the purposes of incentive travel pattern and resulting of three new incentive tour packages.